2016
DOI: 10.12714/egejfas.2016.33.4.14
|View full text |Cite
|
Sign up to set email alerts
|

Age, growth and mortality rates of discard species (Uranoscopus scaber, Neogobius melanostomus and Gobius niger) in the Black Sea

Abstract: Uranoscopus scaber, Neogobius melanostomus and Gobius niger are called non-commercial fish species and also caught as discarded in Turkish fisheries. Samplings were carried out by bottom trawl, gillnet, purse seine net operations in the Turkish Black Sea coasts. The results of the study showed that age of these species were 0-V ages for Uranoscopus scaber and Gobius niger, and 0-VII ages for Neogobius melanostomus for both sexes. The von Bertalanffy growth parameters, total mortality rate (Z), natural mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 15 publications
3
8
1
1
Order By: Relevance
“…The instantaneous total mortality rate (Z), natural mortality (M) and fishing mortality (F) were estimated as 0.625, 0.479 and 0.145, respectively. Similarly, Kasapoğlu (2016) found Z=0.54, M=0.29 and F=0.145 in similar study region. Nikolskii (1954) reported that the species reaches sexual maturity at two years old in females and three years old in males.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The instantaneous total mortality rate (Z), natural mortality (M) and fishing mortality (F) were estimated as 0.625, 0.479 and 0.145, respectively. Similarly, Kasapoğlu (2016) found Z=0.54, M=0.29 and F=0.145 in similar study region. Nikolskii (1954) reported that the species reaches sexual maturity at two years old in females and three years old in males.…”
Section: Discussionsupporting
confidence: 67%
“…There are various studies in the regions for this species Abdoli et al, 2009;Yankova et al, 2011, Hôrková andKováč, 2014;Macun, 2017) however studies from the Black Sea, especially the southern part are scarce (Engin, 2008;Gözler et al, 2003;Kurt, 2005;Kasapoğlu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, G. callidus had higher mortality rates compared with G. niger from Turkey (Filiz & Toğulga, 2009), and female Neogobius caspius (Eichwald 1831), however, had low mortality rates than male N. caspius (Aghajanpour et al ., 2016) from the Caspian Sea and Aphia minuta (Risso 1810) from Italy (La Mesa, 1999). Furthermore, N. melanostomus had higher mortality rates than G. callidus (Kasapoğlu, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…(Golani et al., 2006). It is caught by bottom trawl and it has limited commercial value in Turkish seas fishery (Demirhan et al., 2007; Erdoğan Sağlam & Sağlam, 2013; Golani et al., 2006; Kasapoglu, 2016). The maximum total length published for U. scaber is 40.0 cm (Roux, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Although a few studies have been carried out on age and growth of Atlantic stargazer in the Black Sea (Demirhan et al., 2007; Erdoğan Sağlam & Sağlam, 2013; Kasapoglu, 2016), there is no information on the performance of this species along the Mediterranean coasts of Turkey. Rizkalla and Bakhoum (2009) reported some biological aspects from Egyptian waters (Eastern Mediterranean) and only one study exists on the growth of Atlantic stargazer from Tunisian waters in the western Mediterranean (Bondka & Kartas, 1986).…”
Section: Introductionmentioning
confidence: 99%